Cervical Cancer Screening Cascade for women living with HIV: a cohort study from Zimbabwe. - Katayoun Taghavi; Ardele Mandiriri; Tinei Shamu; Eliane Rohner; Lukas Bütikofer; Serra Asangbeh; Tsitsi Magure; Cleophas Chimbetete; Matthias Egger; Margaret Pascoe; Julia Bohlius (PLOS Global Public Health, 2022)
Countries with high HIV prevalence, predominantly in sub-Sahahran Africa, have the highest cervical cancer rates globally. HIV care cascades successfully facilitated the scale-up of antiretroviral therapy. A cascade approach could similarly succeed to scale-up cervical cancer screening, supporting WHO's goal to eliminate cervical cancer. We defined a Cervical Cancer Screening Cascade for women living with HIV (WLHIV), evaluating the continuum of cervical cancer screening integrated into an HIV clinic in Zimbabwe. We included WLHIV aged ≥18 years enrolled at Newlands Clinic in Harare from June 2012-2017 and followed them until June 2018. We used a cascade approach to evaluate the full continuum of secondary prevention from screening to treatment of pre-cancer and follow-up. We report percentages, median time to reach cascade stages, and cumulative incidence at two years with 95% confidence intervals (CI). We used univariable Cox proportional hazard regressions to calculate cause-specific hazard ratios with 95% CIs for factors associated with completing the cascade stages. We included 1624 WLHIV in the study. The cumulative incidence of cervical screening was 85.4% (95% CI 83.5-87.1) at two years. Among the 396 WLHIV who received screen-positive tests in the study, the cumulative incidence of treatment after a positive screening test was 79.5% (95% CI 75.1-83.2) at two years. The cumulative incidence of testing negative at re-screening after treatment was 36.1% (95% CI 31.2-40.7) at two years. Using a cascade approach to evaluate the full continuum of cervical cancer screening, we found less-than 80% of WLHIV received treatment after screen-positive tests and less-than 40% were screen-negative at follow-up. Interventions to improve linkage to treatment for screen-positive WLHIV and studies to understand the clinical significance of screen-positive tests at follow-up among WLHIV are needed. These gaps in the continuum of care must be addressed in order to prevent cervical cancer.